Quantitative Investigation of the Size-dependent Aggregation of Nanoplastics - Tingting HU; Zhixiong LI; Jiawei CHEN (Yankuang ceshi)
The geochemical behavior of microplastics (MPs) and nanoplastics (NPs) in the environment has become a global hot topic. Aggregation effect is an important factor controlling the geochemical behavior of NPs, yet there is conflicting evidence regarding the dependence of aggregation on NPs size. Investigating the general patterns and dominant mechanisms governing the aggregation behavior of different-sized NPs under various environmental conditions, will provide help in understanding and predicting the fate of NPs with different sizes. The study has shown that NPs with the same chemical composition but different sizes have different stability and mobility under the same conditions. The critical coagulation concentration (CCC) for NPs increases with the decrease in particle size at a fixed surface ζ potential (CCC=325mmol/L, 296mmol/L, 264mmol/L for 50nm, 100nm, and 200nm, respectively); indicating smaller NPs may transport longer distances. As the pH increased from 5.5 to 7, the negative surface charge of 100 and 200nm NPs allowed them to remain stable even at higher ionic strength. However, 50 nm NPs underwent rapid aggregation because of its smaller ζ potential. Therefore, the effects of pH, ionic strength and NPs sizes should be considered comprehensively in predicting and evaluating the geochemical behavior of NPs in the natural environment. The BRIEF REPORT is available for this paper at http://www.ykcs.ac.cn/en/article/doi/10.15898/j.ykcs.202305020058.